2023
DOI: 10.1101/2023.10.01.23296379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the aetiological foundations of the heart failure spectrum using human genetics

Albert Henry,
Xiaodong Mo,
Chris Finan
et al.

Abstract: Summary paragraphHeart failure (HF), a syndrome of symptomatic fluid overload due to cardiac dysfunction, is the most rapidly growing cardiovascular disorder. Despite recent advances, mortality and morbidity remain high and treatment innovation is challenged by limited understanding of aetiology in relation to disease subtypes. Here we harness the de-confounding properties of genetic variation to map causal biology underlying the HF phenotypic spectrum, to inform the development of more effective treatments. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…We used LocusZoom, eQTLs, and transcriptome-wide association study to prioritise genes at each locus. The identified associations include loci of definitive evidence cardiomyopathy-associated genes ( TNNT2, TTN, PLN ) and colocalise with recent HCM (e.g., TBX3, STRN, MTSS1 26 ), DCM (e.g., PKD1, STRN, MITF, CDKN1A 27 ), and heart failure GWAS 28 . For sensitivity analyses, we removed any individuals in the UK Biobank who had a diagnosis of any cardiomyopathy or heart failure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used LocusZoom, eQTLs, and transcriptome-wide association study to prioritise genes at each locus. The identified associations include loci of definitive evidence cardiomyopathy-associated genes ( TNNT2, TTN, PLN ) and colocalise with recent HCM (e.g., TBX3, STRN, MTSS1 26 ), DCM (e.g., PKD1, STRN, MITF, CDKN1A 27 ), and heart failure GWAS 28 . For sensitivity analyses, we removed any individuals in the UK Biobank who had a diagnosis of any cardiomyopathy or heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…Hyper-and hypo-trabeculation were deemed > or < 1.5 standard deviations from the mean. Mendelian randomization was assessed using GWAS Summary statistics from published literature [26][27][28] with mean global FD using the R packages TwoSampleMR and MVMR. Exposure variants were included if GWAS significant (P<5x10 −8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al (2020) conducted a meta-analysis of HF GWAS using data from 29 studies encompassing 47,309 cases and 930,014 controls [39]. 11 genomic loci reached genome-wide significance (P < 5 × 10 −8 ; Table 1 [39][40][41][42]). Many of the loci identified have strong associations with cardiovascular disease risk factors such as FTO (fat mass and obesity-associated; associated with BMI), PITX2 (the PITX2 transcription factor; associated with atrial fibrillation [AF]), and LPA (lipoprotein(a); associated with coronary artery disease [CAD]).…”
mentioning
confidence: 99%
“…Henry et al ( 2023) reported a GWAS meta-analysis on a cohort of 1.9 million ancestrally diverse people, including 153,174 cases of HF [42]. They identified 66 genetic susceptibility loci across HF subtypes (Table 1).…”
mentioning
confidence: 99%